IMAGE-BASED MADRASAH CHANGE MANAGEMENT; THE ANALYSIS OF INSTITUTIONAL READINESS AND STRATEGIC INNOVATION - Nuriyah, Khalisatun; Jazilurrahman, Jazilurrahman; Ulum, Moh.; Firdaus, Sulton (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islamic boarding school-based change management has become relevant in dealing with global dynamics and societal development. This research aims to analyze the readiness of Islamic boarding school institutions to implement change management and identify innovative strategies that can be implemented. The research method involves surveys and interviews with various related parties in Islamic boarding school institutions. The results of the analysis show that the readiness of Islamic boarding school institutions to change still has challenges, including cultural, leadership, and infrastructure factors. Therefore, innovation strategies need to be implemented holistically to increase the readiness of Islamic boarding school institutions to face change. The proposed innovative strategies include developing leadership training programs, integrating technology in the learning process, and strengthening Islamic boarding school values globally. In addition, inter-institutional cooperation and community empowerment were also identified as key factors in increasing the readiness of Islamic boarding school institutions for change. This research contributes to the development of an Islamic boarding school-based change management model that similar institutions can adopt. The practical implication of these findings is the need for support from the government, stakeholders, and communities in increasing the readiness of Islamic boarding school institutions to adapt to changes in the continuously developing global context.